2004
DOI: 10.1158/1078-0432.ccr-04-0983
|View full text |Cite
|
Sign up to set email alerts
|

The CC Chemokine Receptor 4 as a Novel Specific Molecular Target for Immunotherapy in Adult T-Cell Leukemia/Lymphoma

Abstract: Adult T-cell leukemia/lymphoma (ATLL) is a peripheral T-cell neoplasm with dismal prognosis, and no optimal therapy has been developed. We tested the defucosylated chimeric anti-CC chemokine receptor 4 (CCR4) monoclonal antibody, KM2760, to develop a novel immunotherapy for this refractory tumor. In the presence of peripheral blood mononuclear cells (PBMCs) from healthy adult donors, KM2760 induced CCR4-specific antibody-dependent cellular cytotoxicity (ADCC) against CCR4-positive ATLL cell lines and primary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 140 publications
(146 citation statements)
references
References 48 publications
(31 reference statements)
9
135
1
1
Order By: Relevance
“…We have previously reported that the level of FOXP3 mRNA in CD4 1 CCR4 1 and CD4 1 CD25 1 cells in healthy individuals is very similar. 6 Also as reported previously, 6 the level of FOXP3 expression in control CD4 1 CCR4 2 cells was low (2.6 6 0.7, Fig. 2b).…”
Section: Foxp3 Expression In Atll Cellssupporting
confidence: 83%
See 2 more Smart Citations
“…We have previously reported that the level of FOXP3 mRNA in CD4 1 CCR4 1 and CD4 1 CD25 1 cells in healthy individuals is very similar. 6 Also as reported previously, 6 the level of FOXP3 expression in control CD4 1 CCR4 2 cells was low (2.6 6 0.7, Fig. 2b).…”
Section: Foxp3 Expression In Atll Cellssupporting
confidence: 83%
“…Recently, several investigators including ourselves have reported that FOXP3, which is a master control gene for the development and function of CD4 1 CD25 1 naturally occurring regulatory T (Treg) cells, [2][3][4] is expressed in the tumor cells from a subset of patients with ATLL. [5][6][7][8][9][10] Furthermore, we and other investigators have reported that ATLL cells from most patients express CCR4, 11,12 and very recently, Hirahara et al reported that virtually all peripheral blood CD4 1 CD25 high Foxp3 1 Treg cells express high levels of CCR4. 13 Collectively, because most ATLL cells express both CD4 and CD25, 1 based on their phenotypic characteristics, these tumors might originate from CD4 1 CD25 1 FOXP3 1 CCR4 1 Treg cells.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Therefore, depletion of Treg cells in the vicinity of tumors is a potentially promising strategy for boosting tumor-associated Agspecific immunity (35)(36)(37)(38). We have shown that a therapeutic anti-CCR4 mAb does deplete Treg cells in vitro (39,40) and in vivo in humanized mice (27). Furthermore, we confirmed the CD25 + CD4 + FOXP3 + Treg depletion activity mediated by the humanized anti-CCR4 mAb mogamulizumab (KW-0761) in humans (41)(42)(43)(44).…”
Section: Discussionsupporting
confidence: 63%
“…Antibody therapy against ATL cells has advantages due to its decreased adverse effects. As described above, most ATL cells express CCR4 antigen on their surfaces, and a humanized antibody against CCR4 is being developed as an anti-ATL agent (Ishida et al 2004). Advances in the treatment of ATL were brought about by allogeneic bone marrow or stem cell transplantation (Borg et al 1996;Yamada et al 2001).…”
Section: Atl Treatment: Current State and New Strategiesmentioning
confidence: 99%